Full-biodegradable corrugated board adhesive and preparation method thereof

By introducing surface saccharified fine straw powder into the starch glue, combining cellulase and redispersible latex powder, the problems of adhesive viscosity instability and water permeability are solved, and the high-speed production stability of corrugated cardboard is achieved and The bonding strength reduces the amount of borax used and improves the biodegradability of the adhesive.

CN119144279APending Publication Date: 2024-12-17TAIZHOU FULIAN PACKAGE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411491326.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

During the bonding process of corrugated paper, existing starch adhesives have problems such as unstable viscosity, water passing through, resulting in contamination and warping of surface paper, and the use of high borax causes the adhesive to become brittle and explosive, making it difficult to meet the high-speed production. need.

Method used

Using the fully biodegradable corrugated cardboard adhesive preparation method, the cleaned and removed straw is refined into fine powder, and combined with starch, cellulase, redispersible latex powder, etc., and the surface saccharification and stirring are formed. Large molecular structure with stable viscosity and good permeability reduces the use of borax.

Benefits of technology

The viscosity stability, permeability and quick drying of the adhesive are achieved, and the problems of surface paper are avoided, warping and brittle, and the production stability and bonding strength of corrugated cardboard are improved, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144279A_ABST
    Figure CN119144279A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and particularly discloses a full-biodegradable corrugated board adhesive and a preparation method thereof. The preparation method of the adhesive comprises the following steps: preparing surface saccharification straw slurry; preparing starch glue from water, starch, redispersible latex powder, polyvinyl alcohol powder and caustic soda flakes; uniformly mixing starch glue and the surface saccharified straw slurry, stirring and defoaming; and adding borax to adjust the viscosity to obtain the full-biodegradable corrugated board adhesive. According to the adhesive, surface-saccharified straw fine powder is introduced into a starch glue system, the surface-saccharified straw fine powder has certain adhesion, excellent adsorbability, good fluidity and easiness in coating, and while the adhesion is assisted, the fine straw is of a fiber structure and has rich micropores, so that the viscosity stability can be maintained; the usage amount of borax is reduced. And water in the adhesive is prevented from being excessively adsorbed and permeated by coarse pores of the corrugated peaks, so that the high-speed corrugated production is more stable, and the surface paper is prevented from penetrating through the bottom, warping and wrinkling. The preparation process is simple and easy to control, can be prepared at any time, and can also be prepared in advance for long-term storage and use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, relates to adhesive technology for corrugated paper, and specifically relates to a fully biodegradable corrugated paperboard adhesive and a preparation method thereof. Background Art

[0002] As a widely used packaging material, corrugated paperboard is being used more and more. Therefore, the corrugated paper industry has increasingly stringent requirements in terms of controlling raw material costs, increasing production capacity, and environmental performance. Corrugated paper is generally made of at least one layer of corrugated paper core and surface paper bonded together. The performance of the adhesive used in large quantities directly determines the quality of the corrugated paper, especially the performance of the adhesive directly affects the production speed, quick drying effect, bonding strength, water resistance, warping, etc. of the corrugated paper.

[0003] The earliest corrugated paper adhesive used was sodium carbonate, and its aqueous solution was water glass. As a corrugated paper adhesive, water glass has low cost and high bonding strength, but it has obvious defects, mainly poor water resistance, easy moisture absorption, and certain corrosiveness. It has been eliminated. High molecular polymer emulsion adhesives have good comprehensive performance, high bonding strength and water resistance, but high cost and poor degradability. Therefore, they are mainly used in corrugated paper with special needs. Starch adhesives mainly use starch as raw material. The raw material supply is abundant and the cost is low. In addition, the production technology of starch glue is simple and the product is environmentally friendly. It is the mainstream of corrugated paper adhesives at present and has a large demand.

[0004] The current starch adhesive technology is mainly a system based on corn starch, water, caustic soda and borax. The principle of using starch glue to bond corrugated paper on the sewing line is to use the micropores of the paper. The adhesive quickly penetrates into the micropores and the steam temperature of the external cardboard causes the starch glue to quickly gelatinize, bond and solidify.

[0005] However, there are still many problems with the existing starch adhesives in corrugated bonding. Generally, starch glue contains more water, and the micropores of paper are open-pore structures. When starch glue is bonded, the water in the adhesive easily penetrates the paper excessively, causing water to pass through the surface paper to pollute the surface of the corrugated paper, and even excessive absorption of water by the surface paper causes the paperboard to warp and wrinkle. In addition, the viscosity of the adhesive thickened by a large amount of borax crosslinking agent is extremely unstable. The unstable viscosity of the adhesive is the key to the production of waste and defective products in corrugated board production. Viscosity control has become a key factor in bonding corrugated paper. At high speeds, low viscosity is generally required to be able to quickly and evenly roll glue, while low-viscosity starch glue is more likely to penetrate the paper, and the flute peaks absorb the adhesive too quickly, resulting in a large amount of water in the adhesive being absorbed and penetrated, resulting in bottom penetration and poor adhesion. Although the viscosity of the adhesive has been increased by adding thickeners, the viscosity stability of the existing thickening is poor. Whether in storage or use, the large fluctuations in viscosity make it more difficult to debug the corrugated line.

[0006] In existing production applications, the viscosity of starch glue is mainly controlled by adding a large amount of borax as a cross-linking agent to increase the viscosity of the adhesive. Although the use of borax can improve the initial viscosity and quick-drying properties of starch adhesives, the starch adhesives that use a large amount of borax have a large change in viscosity during the later storage period and are prone to coagulation and stratification. After use, corrugated cardboard often becomes brittle and cracks. Summary of the invention

[0007] At present, when starch glue is used as an adhesive to bond corrugated paper at high speed, low-viscosity adhesive is easy to flow, but excessive water is absorbed by the paper, resulting in bottom penetration and reduced bonding strength; high-viscosity adhesive is not easy to flow, resulting in the problem of increased coating amount. In view of the above problems, in order to meet the stable production needs of high-speed corrugated paper and better stabilize the viscosity, the present invention proposes a fully biodegradable corrugated paperboard adhesive, which has good full biodegradability and controllable penetration adhesion, viscosity stability and quick drying. Furthermore, a preparation method of the adhesive is provided.

[0008] In order to achieve the above-mentioned technical effects, the technical solution adopted by the present invention is:

[0009] First, a preparation method of a fully biodegradable corrugated cardboard adhesive is provided, and the specific preparation method is as follows:

[0010] S1. The cleaned straw is dried and crushed, and further refined by a vortex airflow refiner to a particle size of less than 50 μm to obtain fine straw powder:

[0011] S2. Add fine straw powder and water in a mass ratio of 1:3-4 into a stirring kettle to form a slurry, add dilute hydrochloric acid to adjust the pH value to between 6.0-6.5, then add cellulase and stir at a low speed for 1-2 hours, let stand for 3-5 hours, heat to 50-60°C and stir to inactivate, to obtain a fine and adhesive surface saccharified straw slurry; the amount of cellulase added is 0.01% by weight of the fine straw powder;

[0012] S3. Add 100 parts of water by weight to a stirring tank, start stirring at a low speed, slowly pour in 20-25 parts of starch and stir evenly; then add 0.3-0.5 parts of redispersible latex powder and 0.2-0.3 parts of polyvinyl alcohol powder and stir evenly at a low speed; further add 0.5-0.75 parts of caustic soda flakes, continue stirring at a low speed, until the slurry begins to turn yellow, add 20-30 parts of the surface saccharified straw slurry of step S2 to a stirring tank, stir at a high speed for 5-8 minutes, add 0.05-0.1 parts of a defoamer, and stir at a low speed to defoam;

[0013] S4. Dissolve 0.05-0.1 parts of borax and 0.5-1 parts of 60°C hot water completely by weight, slowly add into the stirring tank, stir at low speed, take samples every 5 minutes, and use a 4# viscosity cup to detect the viscosity until the viscosity stabilizes, stop stirring, and obtain a fully biodegradable corrugated cardboard adhesive, discharge the material into a storage barrel, and store at 50kg per barrel.

[0014] Preferably, the straw in step S1 is at least one of wheat straw, corn straw, soybean straw, and rice straw, and wheat straw is particularly preferred. Straw is agricultural waste, which is not only low in cost but also has excellent biodegradability. The strong centrifugal force generated by the vortex airflow refiner under the action of the high-speed rotating airflow refines the straw in a suspended state to prevent agglomeration. The refined straw powder is separated by the rotational motion caused by the tangential introduction of the airflow in a cyclone separator to obtain fine straw powder of the desired particle size.

[0015] Preferably, the enzymatic activity of the cellulase in step S2 is 20,000 μ / g, the main components of the straw fine powder are cellulose, hemicellulose and lignin, the cellulase is adsorbed on the surface of the straw fine powder, and the cellulose on the surface of the straw powder is partially hydrolyzed and saccharified, and the hydrolysis time needs to be controlled to prevent excessive hydrolysis, and the preferred hydrolysis time is controlled at 3-5h. The surface saccharified straw powder is sticky, smooth and easy to apply, the overall structure of the straw powder is still fine fiber, the micropores have adsorption and water holding properties, and the viscosity can be adjusted well for starch glue to maintain stable viscosity. After roller coating, the straw powder absorbs water to prevent the moisture in the adhesive from being excessively adsorbed by the facial paper and the peaks, and prevents the bottom from being penetrated. The micropores it has can increase the drying speed.

[0016] Preferably, the starch in step S3 is selected from at least one of corn starch and tapioca starch.

[0017] Preferably, the redispersible latex powder in step S3 is selected from at least one of vinyl acetate homopolymer powder, vinyl acetate and ethylene copolymer powder, acrylate and styrene copolymer powder, and vinyl acetate and acrylate and higher fatty acid vinyl ester ternary copolymer powder; the redispersible latex powder can be quickly redispersed into an emulsion after contacting with water, and since the redispersible latex powder has high bonding ability, it can assist starch and straw powder in improving bonding strength; at the same time, the redispersible latex powder has good water resistance, and after film bonding, it prevents the corrugated bonding surface from being damp; the redispersible latex powder can improve the rheological properties, making it easier to evenly roll the adhesive.

[0018] Preferably, the polyvinyl alcohol powder in step S3 is selected from at least one of PVA2488 and PVA1788, which is used to improve the bonding strength and drying speed of the starch adhesive.

[0019] Preferably, the defoaming agent in step S3 is selected from tributyl phosphate and silicone oil.

[0020] Preferably, the low-speed stirring is carried out at a rotation speed of 50-80 rpm; and the high-speed stirring is carried out at a rotation speed of 300-600 rpm.

[0021] Furthermore, the present invention provides a fully biodegradable corrugated board adhesive prepared by the above method. The surface of fine straw powder is saccharified by cellulase, and the fine straw has adhesive properties and is smooth to apply. The fine straw is a fiber structure with abundant micropores, and has adsorption and water holding properties in the adhesive, maintaining stable viscosity without the need to use a large amount of borax to adjust the viscosity; the surface saccharified straw has abundant micropores that can hold water, preventing the water in the adhesive from being excessively adsorbed and penetrated by the coarse pores of the flute peaks, thereby making the high-speed corrugated production more stable and avoiding bottom see-through, warping, and wrinkling. The introduction of surface saccharified straw fine powder into starch glue not only reduces costs and is easy to biodegrade, but also easily forms a whole with the coarse fibers of the flute peaks of corrugated paper, avoiding degumming.

[0022] Compared with the prior art, the present invention has the following outstanding features and significant advantages:

[0023] 1. The present invention introduces surface saccharified straw fine powder into the starch glue system. The surface saccharified straw fine powder has certain adhesion and excellent adsorption, good fluidity and is easy to apply. While assisting the adhesion, the fine straw is a fiber structure with abundant micropores, which can maintain stable viscosity in the adhesive and reduce the amount of borax used.

[0024] 2. The surface saccharified straw powder of the present invention has abundant micropores that can hold water, preventing the water in the adhesive from being excessively adsorbed and penetrated by the coarse pores of the flute peaks, thereby making the high-speed corrugated production more stable and avoiding the bottom see-through, warping and wrinkling of the surface paper.

[0025] 3. The present invention only partially hydrolyzes the fine straw powder, and the processing process is simple and has low requirements. Introducing it into starch glue not only reduces the cost and is easy to biodegrade, but also the fiber-structured straw powder and the flute crude fiber of the corrugated paper can easily form a whole, further enhancing the adhesion and avoiding degumming.

[0026] 4. The preparation process of the adhesive of the present invention is simple and easy to control. It can be prepared as needed or prepared in advance for long-term storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to further clarify the uniformity of the adhesive coating of the present invention, the present invention is further described below in conjunction with the accompanying drawings:

[0028] Figure 1 This is the glue line diagram of the adhesive roller coating peak of Example 2.

[0029] Figure 2 This is the glue line diagram of the adhesive roller coating peak of Comparative Example 3. DETAILED DESCRIPTION

[0030] The following examples are intended to further describe the implementation process of the technical content of the present invention, but are not intended to limit the scope of protection of the claims of the present invention. If no specific conditions are specified in the examples, conventional process conditions are used.

[0031] Example 1

[0032] S1. The cleaned wheat straw is dried, crushed into coarse powder by a pulverizer, and then sent to a vortex airflow refiner. The main engine speed is controlled to 800rpm. The vortex airflow refiner generates a strong centrifugal force under the action of high-speed rotating airflow, and the straw is refined in a suspended state to prevent agglomeration. The refined straw powder is passed through a cyclone separator, and the classifier speed is adjusted to 1100rpm to obtain fine straw powder with a particle size of less than 50μm:

[0033] S2. Add fine straw powder and water in a mass ratio of 1:3 into a stirring kettle to form a slurry, add dilute hydrochloric acid to adjust the pH value to between 6.0 and 6.5, then add cellulase and stir at a low speed of 50 rpm for 1 hour, let stand for 3 hours, heat to 60°C and stir to inactivate, so that the surface layer of the fine straw powder is partially hydrolyzed and saccharified to obtain a fine and adhesive surface saccharified straw slurry; the enzyme activity level of the cellulase is 20,000 μ / g, and the amount added is 0.01% of the weight of the fine straw powder;

[0034] S3. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour in 22 parts of corn starch while stirring; then add 0.3 parts of redispersible latex powder acrylate and styrene copolymer powder, 0.2 parts of Sichuan Wei's 1788 polyvinyl alcohol powder and stir at a low speed; further add 0.6 parts of caustic soda, continue stirring at a low speed, until the slurry begins to turn yellow, add 25 parts of the surface saccharified straw slurry of step S2 to a stirring tank, stir at a high speed of 300rpm for 8min, add 0.1 parts of defoaming agent tributyl phosphate, and stir at a low speed of 50rpm to defoam;

[0035] S4. Dissolve 0.08 parts of borax and 0.5 parts of 60°C hot water completely by weight, slowly add into the stirring tank, stir at a low speed of 50rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and use a stopwatch to measure the time required for the adhesive to flow out as the viscosity. The viscosities after stirring for 5min, 10min, 15min, and 20min are 21s, 23s, 26s, and 26s respectively. After stirring for 20min, the viscosity is stable, stop stirring, and obtain a fully biodegradable corrugated cardboard adhesive. Discharge the material into a storage barrel and store it at 50kg per barrel.

[0036] Example 2

[0037] S1. The cleaned corn stalks are dried, crushed into coarse powder by a pulverizer, and then sent to a vortex airflow refiner. The main engine speed is controlled to 800rpm. The vortex airflow refiner generates a strong centrifugal force under the action of high-speed rotating airflow, which refines the stalks in a suspended state to prevent agglomeration. The refined stalk powder passes through a cyclone separator and the classifier speed is adjusted to 1200rpm to obtain fine stalk powder with a particle size of less than 50μm:

[0038] S2. Add fine straw powder and water in a mass ratio of 1:3.5 into a stirring kettle to form a slurry, add dilute hydrochloric acid to adjust the pH value to between 6.0 and 6.5, then add cellulase and stir at a low speed of 50 rpm for 1 hour, let stand for 4 hours, heat to 60°C and stir to inactivate, so that the surface layer of the fine straw powder is partially hydrolyzed and saccharified to obtain a fine and adhesive surface saccharified straw slurry; the enzyme activity level of the cellulase is 20,000 μ / g, and the amount added is 0.01% of the weight of the fine straw powder;

[0039] S3. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour in 22 parts of cassava starch while stirring; then add 0.4 parts of redispersible latex powder of vinyl acetate and ethylene copolymer powder, and 0.2 parts of Sichuan Wei's 1788 polyvinyl alcohol powder and stir at a low speed; further add 0.5 parts of caustic soda, continue stirring at a low speed, and wait until the slurry begins to turn red and yellow, add 30 parts of the surface saccharified straw slurry of step S2 to a stirring tank, stir at a high speed of 400rpm for 5min, add 0.1 parts of defoaming agent tributyl phosphate, and stir at a low speed of 50rpm to defoam;

[0040] S4. Dissolve 0.1 parts of borax and 1 part of 60°C hot water completely according to weight, slowly add into the stirring tank, stir at a low speed of 50rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and use a stopwatch to measure the time required for the adhesive to flow out as the viscosity. The viscosity after stirring for 5min, 10min, and 15min is 30s, 34s, and 34s respectively. After stirring for 15min, the viscosity is stable, stop stirring, and obtain a fully biodegradable corrugated cardboard adhesive. Discharge the material into a storage barrel and store it at 50kg per barrel.

[0041] Example 3

[0042] S1. The cleaned wheat straw is dried, crushed into coarse powder by a pulverizer, and then sent to a vortex airflow refiner. The main engine speed is controlled to 800rpm. The vortex airflow refiner generates a strong centrifugal force under the action of high-speed rotating airflow, and the straw is refined in a suspended state to prevent agglomeration. The refined straw powder is passed through a cyclone separator, and the classifier speed is adjusted to 1100rpm to obtain fine straw powder with a particle size of less than 50μm:

[0043] S2. Add fine straw powder and water in a mass ratio of 1:3 into a stirring kettle to form a slurry, add dilute hydrochloric acid to adjust the pH value to between 6.0 and 6.5, then add cellulase and stir at a low speed of 50 rpm for 1 hour, let stand for 3 hours, heat to 60°C and stir to inactivate, so that the surface layer of the fine straw powder is partially hydrolyzed and saccharified to obtain a fine and adhesive surface saccharified straw slurry; the enzyme activity level of the cellulase is 20,000 μ / g, and the amount added is 0.01% of the weight of the fine straw powder;

[0044] S3. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour in 22 parts of corn starch while stirring; then add 0.5 parts of redispersible latex powder vinyl acetate homopolymer powder and 0.3 parts of Ningxia Dadi 2488 polyvinyl alcohol powder and stir at a low speed; further add 0.7 parts of caustic soda, continue stirring at a low speed, and wait until the slurry begins to turn yellow. 30 parts of the surface saccharified straw slurry of step S2 are added to a stirring tank, stirred at a high speed of 500rpm for 8min, and 0.1 parts of defoaming agent silicone oil are added, and defoaming is stirred at a low speed of 50rpm;

[0045] S4. Dissolve 0.1 parts of borax and 1 part of 60°C hot water completely according to weight, slowly add into the stirring tank, stir at a low speed of 50rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and use a stopwatch to measure the time required for the adhesive to flow out as the viscosity. The viscosity after stirring for 5min, 10min, 15min, and 20min is 30s, 32s, 37s, and 37s respectively. After stirring for 20min, the viscosity is stable, stop stirring, and obtain a fully biodegradable corrugated cardboard adhesive. Discharge the material into a storage barrel and store it at 50kg per barrel.

[0046] Comparative Example 1

[0047] S1. The cleaned wheat straw is dried, crushed into coarse powder by a pulverizer, and then sent to a vortex airflow refiner. The main engine speed is controlled to 800rpm. The vortex airflow refiner generates a strong centrifugal force under the action of high-speed rotating airflow, and the straw is refined in a suspended state to prevent agglomeration. The refined straw powder is passed through a cyclone separator, and the classifier speed is adjusted to 1100rpm to obtain fine straw powder with a particle size of less than 50μm:

[0048] S2. Add fine straw powder and water in a mass ratio of 1:3 into a stirring tank to form a fine straw slurry;

[0049] S3. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour in 22 parts of corn starch while stirring; then add 0.3 parts of redispersible latex powder acrylate and styrene copolymer powder, 0.2 parts of Sichuan Wei's 1788 polyvinyl alcohol powder and stir at a low speed; further add 0.6 parts of caustic soda, continue stirring at a low speed, until the slurry begins to turn yellow, add 25 parts of the fine straw slurry of step S2 to a stirring tank, stir at a high speed of 300rpm for 8min, add 0.1 parts of defoaming agent tributyl phosphate, and stir at a low speed of 50rpm to defoam;

[0050] S4. Dissolve 0.08 parts of borax and 0.5 parts of 60°C hot water completely by weight, slowly add into a stirring tank, stir at a low speed of 50 rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and start timing with a stopwatch. Measure the time required for the adhesive to flow out as the viscosity. The viscosities after stirring for 5 minutes, 10 minutes, 15 minutes, and 20 minutes are 19 seconds, 20 seconds, 21 seconds, and 21 seconds, respectively. After stirring for 20 minutes, the viscosity is stable, and stirring is stopped to obtain a fully biodegradable corrugated cardboard adhesive.

[0051] Compared with Example 1, the fine straw powder in this solution is not pre-treated by saccharification. The problem of bottom penetration can still be solved, and the storage viscosity stability is good. The roller coating sliding property is slightly poor, and the bonding strength is reduced.

[0052] Comparative Example 2

[0053] S1. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour 22 parts of corn starch and stir evenly while stirring; then add 0.3 parts of redispersible latex powder acrylate and styrene copolymer powder, 0.2 parts of Sichuan Wei's 1788 polyvinyl alcohol powder and stir evenly at a low speed; further add 0.6 parts of caustic soda, continue stirring at a low speed, and when the slurry begins to turn yellow, add 0.1 parts of defoaming agent tributyl phosphate, and stir at a low speed of 50rpm to defoam;

[0054] S2. Dissolve 0.08 parts of borax and 0.5 parts of 60°C hot water completely by weight, slowly add into a stirring tank, stir at a low speed of 50 rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and use a stopwatch to measure the time required for the adhesive to flow out as the viscosity. The viscosities after stirring for 5 minutes, 10 minutes, and 15 minutes are 17 seconds, 19 seconds, and 19 seconds respectively. After stirring for 15 minutes, the viscosity is stable, and stirring is stopped to obtain a fully biodegradable corrugated cardboard adhesive.

[0055] Compared with Example 1, this solution does not use saccharified fine straw powder. When the adhesive is used to bond corrugated paper, there is an obvious phenomenon of water absorption and penetration, the viscosity stability is significantly reduced, and the paperboard is warped.

[0056] Comparative Example 3

[0057] S1. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour 22 parts of corn starch and stir evenly while stirring; then add 0.3 parts of redispersible latex powder acrylate and styrene copolymer powder, 0.2 parts of Sichuan Wei's 1788 polyvinyl alcohol powder and stir evenly at a low speed; further add 0.6 parts of caustic soda, continue stirring at a low speed, and when the slurry begins to turn yellow, add 0.1 parts of defoaming agent tributyl phosphate, and stir at a low speed of 50rpm to defoam;

[0058] S2. Dissolve 0.5 parts of borax and 2.5 parts of 60°C hot water completely by weight, slowly add into a stirring tank, stir at a low speed of 50 rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and start timing with a stopwatch. The time required for the adhesive to flow out is measured as the viscosity. The viscosities after stirring for 5 minutes, 10 minutes, 15 minutes, 20 minutes, and 25 minutes are 20 seconds, 24 seconds, 27 seconds, 32 seconds, and 32 seconds, respectively. After stirring for 25 minutes, the viscosity is stable, and stirring is stopped to obtain a fully biodegradable corrugated cardboard adhesive.

[0059] Compared with Example 1, this solution does not use saccharified fine straw powder, and increases the amount of borax to increase the viscosity. During the storage process, the viscosity of the adhesive initially increases significantly with the storage time, mainly because of the deep cross-linking caused by the large amount of borax, which increases the viscosity. In the later period, the viscosity decreases, which is mainly due to the hydrolysis of starch by sodium hydroxide. Due to the unstable viscosity, the designed viscosity and the viscosity required for production cannot be stably controlled, resulting in unstable production, and the viscosity needs to be adjusted on site during later use. When the adhesive is used to bond corrugated paper, there is an obvious phenomenon of water absorption and penetration, and the coating smoothness is poor, which can easily lead to uneven roller coating; and the bonding parts of the corrugated board are prone to brittleness and easy to break when folded.

[0060] Comparative Example 4

[0061] S1. The cleaned wheat straw is dried, crushed into coarse powder by a pulverizer, and then sent to a vortex airflow refiner. The main engine speed is controlled to 800rpm. The vortex airflow refiner generates a strong centrifugal force under the action of high-speed rotating airflow, and the straw is refined in a suspended state to prevent agglomeration. The refined straw powder is passed through a cyclone separator, and the classifier speed is adjusted to 1100rpm to obtain fine straw powder with a particle size of less than 50μm:

[0062] S2. Add fine straw powder and water in a mass ratio of 1:3 into a stirring kettle to form a slurry, add dilute hydrochloric acid to adjust the pH value to between 6.0 and 6.5, then add cellulase and stir at a low speed of 50 rpm for 1 hour, let stand for 3 hours, heat to 60°C and stir to inactivate, so that the surface layer of the fine straw powder is partially hydrolyzed and saccharified to obtain a fine and adhesive surface saccharified straw slurry; the enzyme activity level of the cellulase is 20,000 μ / g, and the amount added is 0.01% of the weight of the fine straw powder;

[0063] S3. Add 100 parts of water by weight to a stirring tank, open it, stir at a low speed of 80rpm, and slowly pour in 22 parts of corn starch while stirring; then add 0.3 parts of redispersible latex powder acrylate and styrene copolymer powder, 0.2 parts of Sichuan Wei's 1788 polyvinyl alcohol powder and stir at a low speed; further add 0.6 parts of caustic soda, continue stirring at a low speed, until the slurry begins to turn yellow, add 25 parts of the surface saccharified straw slurry of step S2 to a stirring tank, stir at a high speed of 300rpm for 8min, add 0.1 parts of defoaming agent tributyl phosphate, and stir at a low speed of 50rpm to defoam;

[0064] S4. Dissolve 0.5 parts of borax and 2.5 parts of 60°C hot water completely according to weight, slowly add into a stirring tank, stir at a low speed of 50 rpm, take samples every 5 minutes to test the viscosity, use a 4# viscosity cup, pour the adhesive into the 4# viscosity cup, release your fingers, and start timing with a stopwatch. Measure the time required for the adhesive to flow out as the viscosity. The viscosities after stirring for 5 minutes, 10 minutes, 15 minutes, and 20 minutes are 24 seconds, 28 seconds, 38 seconds, and 38 seconds, respectively. After stirring for 20 minutes, the viscosity is stable, and stirring is stopped to obtain a fully biodegradable corrugated cardboard adhesive.

[0065] This scheme is based on the scheme of Example 1, and increases the amount of borax to increase the viscosity. When the adhesive is used to bond corrugated paper, due to the presence of fine straw, the phenomenon of water absorption and penetration is eliminated, and there is a certain burst line when it is pressed heavily or folded.

[0066] Viscosity stability test:

[0067] The adhesives of Examples 1-3 and Comparative Examples 1-4 were stored in sealed barrels and placed indoors (ambient temperature 25-27°C). The viscosity values ​​and adhesive states of the 4# viscosity cups were tested after 1 day, 4 days, 7 days, and 30 days. The test data are shown in Table 1:

[0068] Table 1:

[0069]

[0070] It can be seen from Table 1 that the obvious difference is that the adhesives of Comparative Examples 2 and 3 do not use fine straw powder, and the viscosity stability is poor; especially in Comparative Example 3, after using more borax to increase the viscosity, the viscosity line of the adhesive increases significantly during storage, and then decreases significantly, the viscosity stability is poor, and the adhesive is prone to crusting on the surface during long-term storage.

[0071] Bonding corrugated effect test:

[0072] The adhesives of Examples 1-3 and Comparative Examples 1-4 were used to bond corrugated paperboards. The corrugated paperboards were produced at a medium-high speed of 150 m / min on the corrugated line. The surface paper was 175 g / m2 of noodle paper (ring pressure index 7.5 N·m / g). The bonding effect of the corrugated paper was verified by manual peeling to observe whether the surface paper was completely peeled off; observe whether the bottom was exposed and wrinkles were caused by excessive water absorption; and the folding method was used to check the bursting of the line, as shown in Table 2:

[0073] Table 2:

[0074]

[0075] By comparison in Table 2, the present invention introduces surface saccharified straw fine powder into the starch glue system. The surface saccharified straw fine powder has certain adhesion and excellent adsorption, good fluidity, and while assisting adhesion, the fine straw is a fiber structure with abundant micropores, which can maintain stable viscosity in the adhesive and reduce the amount of borax used. The surface saccharified straw has abundant micropores that can hold water, preventing the water in the adhesive from being excessively adsorbed and penetrated by the flute peak coarse pores, thereby making the high-speed corrugated production more stable and avoiding the bottom penetration, warping, and wrinkling of the face paper.

[0076] Adhesive roller coating uniformity test:

[0077] Corrugated paper with similar viscosity in Example 2 and Comparative Example 3 were selected for high-speed bonding to compare the uniformity of adhesive roller coating. The surface paper was peeled off by soaking in water, and diluted iodine solution was sprayed on the surface paper to make the glue line clearly visible.

[0078] The adhesive roller coating peak of Example 2 is reflected on the glue line of the surface paper with uniform thickness and no breakpoints (such as the attached Figure 1 ). This indicates that the adhesive has good fluidity, is smooth and easy to apply, and is suitable for use at high vehicle speeds.

[0079] The adhesive roller coating flute peak of Comparative Example 3 is reflected in the glue line of the surface paper with different thicknesses and a long breakpoint (such as the attached Figure 1 ). This indicates that the adhesive coating adjusted with borax has poor fluidity, which is extremely unfavorable for high-speed corrugated production.

[0080] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a fully biodegradable corrugated cardboard adhesive, the specific preparation method is as follows: S1. The cleaned straw is dried and crushed, and further refined by a vortex airflow refiner to a particle size of less than 50 μm to obtain fine straw powder: S2. Add fine straw powder and water in a mass ratio of 1:3-4 into a stirring kettle to form a slurry, add dilute hydrochloric acid to adjust the pH value to between 6.0-6.5, then add cellulase and stir at a low speed for 1-2 hours, let stand for 3-5 hours, heat to 50-60°C and stir to inactivate, to obtain a fine and adhesive surface saccharified straw slurry; the amount of cellulase added is 0.01% by weight of the fine straw powder; S3. Add 100 parts of water by weight to a stirring tank, start stirring at a low speed, slowly pour in 20-25 parts of starch and stir evenly; then add 0.3-0.5 parts of redispersible latex powder and 0.2-0.3 parts of polyvinyl alcohol powder and stir evenly at a low speed; further add 0.5-0.75 parts of caustic soda flakes, continue stirring at a low speed, until the slurry begins to turn yellow, add 20-30 parts of the surface saccharified straw slurry of step S2 to a stirring tank, stir at a high speed for 5-8 minutes, add 0.05-0.1 parts of a defoamer, and stir at a low speed to defoam; S4. Dissolve 0.05-0.1 parts of borax and 0.5-1 parts of 60°C hot water completely by weight, slowly add into the stirring tank, stir at low speed, take samples every 5 minutes, and use a 4# viscosity cup to detect the viscosity until the viscosity stabilizes, stop stirring, and obtain a fully biodegradable corrugated cardboard adhesive, discharge the material into a storage barrel, and store at 50kg per barrel.

2. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: In step S1, the straw is at least one of wheat straw, corn straw, soybean straw and rice straw.

3. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: The enzymatic activity of the cellulase in step S2 is 20,000 μ / g.

4. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: The starch in step S3 is selected from at least one of corn starch and tapioca starch.

5. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: The redispersible latex powder in step S3 is selected from at least one of vinyl acetate homopolymer powder, vinyl acetate and ethylene copolymer powder, acrylate and styrene copolymer powder, and vinyl acetate, acrylate and higher fatty acid vinyl ester ternary copolymer powder.

6. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: The polyvinyl alcohol powder in step S3 is selected from at least one of PVA2488 and PVA1788.

7. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: The defoaming agent in step S3 is selected from tributyl phosphate and silicone oil.

8. The method for preparing a fully biodegradable corrugated cardboard adhesive according to claim 1, characterized in that: The low-speed stirring is carried out at a rotation speed of 50-80 rpm; the high-speed stirring is carried out at a rotation speed of 300-600 rpm.

9. A fully biodegradable corrugated board adhesive obtained by the preparation method according to any one of claims 1 to 8.